Influencia de la pandemia en la interacción y juego de los niños de educación inicial (Investigaciones) - Castillo Miyasaki, Irene Elvira (2022)
As a result of the pandemic caused by Covid-19, schools were closed in Peru, and children’s possibilities for experiential learning and socialization were reduced. This research investigates preschool teachers’ perceptions of this problem using a qualitative approach and a questionnaire of 54 participants from two Local Educational Management Units of Lima Provinces. Considering that children learn through play, observation, free exploration, and interactions with their peers at preschool, the results show that by limiting these activities due to distance education, children’s learning and socialization and their deployment in different areas of development have been affected.